Proceedings of the 2nd ACM International Workshop on Crowdsourcing for Multimedia 2013
DOI: 10.1145/2506364.2506368
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing-based multimedia subjective evaluations

Abstract: Research on Quality of Experience (QoE) heavily relies on subjective evaluations of media. An important aspect of QoE concerns modeling and quantifying the subjective notions of 'beauty' (aesthetic appeal) and 'something well-known' (content recognizability), which are both subject to cultural and social effects. Crowdsourcing, which allows employing people worldwide to perform short and simple tasks via online platforms, can be a great tool for performing subjective studies in a time and cost-effective way. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the other side, next to the well-established lab tests, crowdsourcing tests are increasing in popularity for such perception tests. For example, it was already shown that crowd sourcing can be used for audio [65,66], video [16,33,82,87,100,105] and image quality assessment [18,37,39,90].…”
Section: Testing Frameworkmentioning
confidence: 99%
“…On the other side, next to the well-established lab tests, crowdsourcing tests are increasing in popularity for such perception tests. For example, it was already shown that crowd sourcing can be used for audio [65,66], video [16,33,82,87,100,105] and image quality assessment [18,37,39,90].…”
Section: Testing Frameworkmentioning
confidence: 99%
“…Further, prior work found that non-expert members of the crowd are able to provide useful aesthetic preference judgements [19,44], and a sub-group of workers on online crowdsourcing platforms enjoy and actively seek out creative tasks [43]. In light of this, researchers and practitioners have explored ways of expanding the feedback elicitation from traditional co-located settings to a crowd of people online.…”
Section: Design Feedback From the Non-expert Crowdmentioning
confidence: 99%
“…In the post-modernist paradigm, crowdsourcing is a subjective being. For example, Redi, Hoßfeld, Korshunov, Mazza, Povoa, and Keimel (2013) found this to be to "a powerful tool for gathering subjective ground truth for large multimedia collections". The foundation here is discourse and it is a tool for describing and presenting reality.…”
Section: The Post-modernist Paradigmmentioning
confidence: 99%